2002
DOI: 10.1152/ajpheart.00046.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction in terms of left ventricular mechanical work and energetics in hypothyroid rats

Abstract: We hypothesized that cardiac dysfunction in hypothyroidism is mainly caused by the impairment of Ca2+ handling in excitation-contraction coupling. To prove this hypothesis, we investigated left ventricular (LV) mechanical work and energetics without interference of preload and afterload in an excised, blood-perfused whole heart preparation from hypothyroid rats. We found that LV inotropism and lusitropism were significantly depressed, and these depressions were causally related to decreased myocardial oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 40 publications
(93 reference statements)
10
58
0
1
Order By: Relevance
“…The slope of the V O 2 -PVA relation remained unchanged in hypothyroid (11) and diabetic (1) rat hearts, whereas a steeper slope of the V O 2 -PVA relation was reported in hyperthyroid rabbit hearts. It was reported that the slope of the V O 2 -PVA relation was related to the ratio of the myosin isoform component from predominantly V3 to predominantly V1 (i.e., the slope of the V O 2 -PVA relation increases when the V1-to-V3 ratio increases, and the slope of the V O 2 -PVA relation is unchanged when the V1-to-V3 ratio decreases) (6).…”
Section: Chemomechanical Energy Transductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The slope of the V O 2 -PVA relation remained unchanged in hypothyroid (11) and diabetic (1) rat hearts, whereas a steeper slope of the V O 2 -PVA relation was reported in hyperthyroid rabbit hearts. It was reported that the slope of the V O 2 -PVA relation was related to the ratio of the myosin isoform component from predominantly V3 to predominantly V1 (i.e., the slope of the V O 2 -PVA relation increases when the V1-to-V3 ratio increases, and the slope of the V O 2 -PVA relation is unchanged when the V1-to-V3 ratio decreases) (6).…”
Section: Chemomechanical Energy Transductionmentioning
confidence: 83%
“…its V O2 intercept represents the PVA-independent V O2. The PVAindependent V O2 is composed of V O2 in excitation-contraction (E-C) coupling (18) and basal metabolism (11,17). The RV was kept collapsed (and therefore unloaded) by continuous hydrostatic drainage of the coronary venous return so that the RV PVA and hence PVA-dependent V O2 were assumed to be negligible (19,20).…”
Section: Mechanical and Energetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the failing heart of hypothyroid rats, the O 2 consumption for total Ca 2? handling in the E-C coupling significantly decreased, but did not increase [40]. Thus, the remodeling of Ca 2?…”
Section: Discussionmentioning
confidence: 83%
“…PVA, which is a total mechanical energy per beat, has been shown to linearly relate with myocardial O 2 consumption per beat in in vitro cross-circulated (blood-perfused) rat hearts [23,40,47]. PVA-independent myocardial O 2 consumption at PVA = 0 corresponds to energy requirements for Ca 2? handling in E-C coupling and basal metabolism [15,23,32].…”
Section: Discussionmentioning
confidence: 99%